Professional identity and work-related quality of life among obstetric nurses: Mediating role of psychological resilience and moderating effect of internet+ participation willingness - Lingling Wu; Weiwei Cai; Fei Wang; Yazhuo Wang; Chang Wang (PLoS ONE, 2025)
Background As the “Internet plus” era unfolds, the domain of obstetric nursing has ushered in the innovative development model of Internet plus Nursing Services(IPNS). This shift has led to alterations in the professional environment and work demands faced by obstetric nursing personnel, consequently bringing the work-related quality of life of these nursing professionals to the forefront of attention. Objective This research aims to investigate the mediating and moderating effects of psychological resilience and the willingness to engage in IPNS among obstetric nurses on the relationship between professional identity and work-related quality of life, under the premise that these factors have a significant impact on work-related quality of life. Methods This study selected obstetric nurses from 33 tertiary hospitals in Anhui Province, China, that have implemented IPNS to date and met the specified criteria for inclusion and exclusion. The assessment focused on their professional identity, psychological resilience, work-related quality of life, and willingness to engage in providing “Internet plus Nursing Services.” AMOS was used for mediation effect analysis, and the PROCESS macro in SPSS was employed to investigate moderated mediation effects. Results In the context of IPNS, psychological resilience acts as a mediator in the relationship between professional identity and work-related quality of life among obstetric nurses. Furthermore, psychological resilience and the willingness to participate exhibit a moderated mediation effect in this relationship—specifically, psychological resilience modulates the latter segment of the pathway from professional identity to work-related quality of life via the mediation of participation willingness. Conclusion The findings suggest that nursing administrators, while focusing on the work-related quality of life of obstetric nurses, should concurrently consider nurses’ psychological resilience and their willingness to participate. This approach facilitates the development of effective employee motivation and support strategies, which in turn can enhance the work-related quality of life of obstetric nurses in the IPNS context.